The Relationship of Family Support with Psychological Conditions and Body Image of Breast Cancer Patients - Nihayati, Hanik Endang; Rohimna, Laksana Rouf; Nastiti, Aria Aulia (International Journal of Psychosocial Rehabilitation, 2020)
Patients with breast cancer will experience psychological stress in the form of depression and anxiety and changes in body shape that will affect the body image of breast cancer patients. Breast cancer patients need external support that can improve their psychological conditions and body image is undergoing treatment that requires a long time. The purpose of this study is to analyze the relationship between family support and psychological conditions and body image of breast cancer patients. The samples obtained were 116 breast cancer patients using purposive sampling. The independent variable is the family support. The dependent variable is a psychological condition and body image. The instruments in this study were in the form of family support questionnaire, psychological distress inventory (PDI) and body image scale (BIS), the data were analyzed with Spearman’s Rho. Breast cancer patients with positive family support were 98 (84.5%) respondents, positive psychological conditions were 91 (78.4%) respondents and positive body image were 94 (81.0%) respondents. There is a relationship between family support with the psychological condition of breast cancer patients (p=0.000. r=0,470) and family support with the body image of breast cancer patients (p=0,000. r=4,00). The role of family support greatly affects the psychological condition and body image of breast cancer patients. Therefore, nurses and other health services can convey to family members to continue to support, motivate and help the needs of breast cancer patients to improve their psychological condition and body image.